Assessment of protective clothing conformity with the requirements of protective clothing standards - Rutić, Srđan Z.; Stojisavljević, Predrag N. (Vojnotehnički glasnik / Military Technical Courier, 2017)
Assessing the compliance of protective clothing is carried out in accordance with the prescribed methods, standards, procedures and criteria in competent laboratories. This paper presents the process of assessing the conformity of the characteristics of special clothing for the protection of the body of the insulating type in accordance with the general requirements of the protective clothing standard (SRPS EN 340: 2007 Protective Clothing, General Requirements). The results presented in the paper indicate that the concept of conformity assessment does not simply involve checking the basic characteristics of a product (purpose, functionality, etc.), but also checking characteristics that are at first glance "of lesser significance" and can influence the safe use of protective clothing.